1995
DOI: 10.1111/j.2044-8341.1995.tb01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do psychiatrists neglect religion?

Abstract: This paper analyses a number of possible reasons why modern psychiatry has neglected the therapeutic effects of religious beliefs. The gap which exists between psychiatry and religion is a relatively recent phenomenon and is partly related to psychiatry's progress in elucidating the biological and psychological causes of mental illness, rendering religious explanations superfluous. In addition, it is often assumed that religious attitudes are inevitably linked with phenomena such as dependence and guilt which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
7

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 19 publications
1
41
0
7
Order By: Relevance
“…It was often assumed that religious attitudes were inevitably the cause of phenomena such as dependence, guilt or delusions (Neeleman and Persaud 1995). Moreover, the gap between psychiatry and religion has widened over the years, partly due to psychiatry's progress in elucidating the biological and psychological causes of mental illness, which have rendered religious explanations more and more superfluous (Payman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was often assumed that religious attitudes were inevitably the cause of phenomena such as dependence, guilt or delusions (Neeleman and Persaud 1995). Moreover, the gap between psychiatry and religion has widened over the years, partly due to psychiatry's progress in elucidating the biological and psychological causes of mental illness, which have rendered religious explanations more and more superfluous (Payman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in religious activities might be associated with a better outcome of schizophrenia [16,17] and depression [11][12][13][14][15]. When psychiatrists see it as one of their tasks to substitute hope for hopelessness, they may be able to learn something from religion, which has many centuries of experience with this problem [2]. A recent controlled study [44] found that highly religious patients with bereavement tended to improve faster when a religious psychotherapy was added to a cognitive-behavioural approach.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Religious beliefs in psychiatric patients are relatively neglected by psychiatrists and psychologists [1][2][3]. This might be partly due to the fact that they are less religiously oriented than their patients and the general population [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…23 These negative attitudes towards religion have influenced many psychiatrists in the 20th century. 24 In 2003, a national random sample of 1,144 U.S. physicians found that psychiatrists were less religious than other physicians. This gap and the lack of training on issues related to R/S and medicine make it more difficult for some psychiatrists to empathize with religious patients and provide appropriate, culturally competent care to these patients.…”
Section: Introductionmentioning
confidence: 99%